Dominant ELOVL1 mutation causes neurological disorder with ichthyotic keratoderma, spasticity, hypomyelination and dysmorphic features. Issue 6 (1st March 2018) - Kutkowska-Kaźmierczak, Anna; Rydzanicz, Małgorzata; Chlebowski, Aleksander; Kłosowska-Kosicka, Kamila; Mika, Adriana; Gruchota, Jakub; Jurkiewicz, Elżbieta; Kowalewski, Cezary; Pollak, Agnieszka; Stradomska, Teresa Joanna; Kmieć, Tomasz; Jakubowski, Rafał; et al.
Abstract : Background: Ichthyosis and neurological involvement occur in relatively few known Mendelian disorders caused by mutations in genes relevant both for epidermis and neural function. Objectives: To identify the cause of a similar phenotype of ichthyotic keratoderma, spasticity, mild hypomyelination (on MRI) and dysmorphic features (IKSHD) observed in two unrelated paediatric probands without family history of disease. Methods: Whole exome sequencing was performed in both patients. The functional effect of prioritised variant in ELOVL1 (very-long-chain fatty acids (VLCFAs) elongase) was analysed by VLCFA profiling by gas chromatography–mass spectrometry in stably transfected HEK2932 cells and in cultured patient's fibroblasts. Results: Probands shared novel heterozygous ELOVL1 p.Ser165Phe mutation (de novo in one family, while in the other family, father could not be tested). In transfected cells p.Ser165Phe: (1) reduced levels of FAs C24:0-C28:0 and C26:1 with the most pronounced effect for C26:0 (P=7.8×10 −6  vs HEK293 cells with wild type (wt) construct, no difference vs naïve HEK293) and (2) increased levels of C20:0 and C22:0 (P=6.3×10 −7, P=1.2×10 −5, for C20:0 and C22:0, respectively, comparison vs HEK293 cells with wt construct; P=2.2×10 −7, P=1.9×10 −4, respectively, comparison vs naïve HEK293). In skin fibroblasts, there was decrease of C26:1 (P=0.014), C28:0 (P=0.001) and increase of C20:0 (P=0.033) in the patient versus controls. There was a strong correlation (r=0.92, P=0.008) between the FAs profile of patient's fibroblasts and that of p.Ser165Phe transfected HEK293 cells. Serum levels of C20:0–C26:0 FAs were normal, but the C24:0/C22:0 ratio was decreased. Conclusion: The ELOVL1 p.Ser165Phe mutation is a likely cause of IKSHD.